The Impact of Divorce on The Social Development of Children 5-6 Years Old: Peter L. Berger's Social Construction Perspective - Karomah, Rosi Tunas; Prasetyo, Andri; Juleha, Siti (PIAUD Universitas Islam Negeri Sunan Kudus, 2023)
Social emotional development of children needs to be given strong support from the family. The condition of an incomplete family will cause differences in aspects of development, one of which is social-emotional in children. The purpose of this paper is to ascertain how children's social development is affected by single parents.The purpose of this paper is to ascertain how children's social development is affected by single parents. Descriptive qualitative method was used. Single parents whose children attend Kindergarten Mentari Ambarawain become research participants. Data collection techniques include interviews, observation, and documentation. The findings of this study have a number of implications for early childhood social and emotional development. Children suffer from low self-esteem, uncontrolled emotions, inability to obey rules, bad behavior, and difficulty adjusting to their environment as a result. The relationship between a single parent and a child will greatly influence the social emotional attitude of the child.